Assessment of Plant Leaves as a Biomonitor for Atmospheric Pollution by Lead in an Arid Environment : A Comparative Study - Bounessah, M.; Al-Shayeb, S.M. (Asian Journal of Chemistry, 2016)
A study is carried out on the possible use of plant leaves as a biomonitor for air pollution by lead in Riyadh City, Saudi Arabia. The distribution of lead concentrations is compared for four plant species in relation to two environmentally different areas (industrial and rural sites). For this, leaves of the following plant species were collected from both sites: Phoenix dactylifera L., Prosopis juliflora, Conorcapus erectus L. and Zizyphus spina christi Jujuba. Results show that the highest average lead levels are found in the industrial site in the leaves of Zizyphus spina christi Jujuba (16.77 g/g) in comparison with Phoenix dactylifera L. (7.45 g/g), Conorcapus erectus L. (12.44 g/g/) and Prosopis juliflora (10.10 g/g). The index of pollution (industrial/rural ratio) showed the highest pollution factor related to Zizyphus spina christi Jujuba (47.91). Results points towards the fact the Zizyphus spina christi Jujuba is the most suitable biomonitor for atmospheric pollution by lead in Riyadh City and areas of the globe with a similar climate.